Two new species in the genus Poikilogyne (Melastomataceae) from Papua New Guinea / N. Cellinese - Cellinese, Nicoletta (2007)
Two new species, Poikilogyne cornuta Cellinese & J: F. Maxwell and P. lakekamuensis Cellinese, are here described. Poikilogyne cornuta is distinct in the genus for the dimorphic anthers and for the peculiar disprity of the connectives and locules. Poikilogyne lakekamuensis is the only vine in the genus having 4-merous flowers. Both species are endemic to Papua New Guinea and know only from a single locality
il.
Keywords: Melastomataceae; Papua Nueva Guinea; Poikilogyne